The Effect of Green Supply Chain Practices on Indonesian Manufacturing Small and Medium Enterprises (SMEs) - Roespinoedji, Roeshartono; Mulyawan, Ferry; Prawira, Afghan; Zainal Abidin, Irwan Shah; Chankoson, Thitinan (ExcelingTech, 2019)
The motivation behind this investigation is to analyze the impact of green SC practices as far as GP, GM and Environment collaborator with suppliers on SCP with the mediating job of op of Indonesian Manufacturing Small and Medium Enterprises (SMEs). This was done quantitatively. 190 example measure was taken from this segment. 5point Likert scale and arbitrary inspecting method was utilized to gather the data. Amos programming was utilized to examine data from respondents. The finish of this examination demonstrated that execution of GSCM exercises, specifically GP, and environmental joint effort with suppliers and GM, decidedly adds to op in manufacturing SMEs. The investigation further presumes that op in manufacturing SMEs in Indonesia decidedly impacts SCP.